Membangun Pemahaman Multikultural dan Multiagama Guna Menangkal Radikalisme di Aceh Singkil - Deny Setiawan; Bahrul Khoir Amal (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2016)
Multicultural education is an educational reform movement. This process is mainly aimed to change the structure of educational institutions. At this stage, students who are members of diverse racial, ethnic, and cultural groups will have an equal chance to achieve better academic values in school. Multi-religion is a situation where there is an existence of some religions in a certain area in which exists in a multi-cultural region. Conflicts which might emerge in Singkil of Aceh are caused by some factors. Among others: lack of the understanding through the existence of multicultural, lack of solidarity among the religious people (multi-religion), and the people from the outside of Aceh Singkil who wants to destroy the stability in this area. Economic disparities and live in poverty for many years is also as another factor rising this conflict, even if it is not the dominant factor.